From Agricultural Roots to Retail Outlets: A Critical Analysis of Price Jumps and Distributional Dynamics in Bangladesh’s Vegetable Markets - Rahaman, Shadikur; Amin, Ruhul (PT. Riset Press International, 2025)
The goal of this study is to determine the individuals and variables causing Bangladesh's vegetable supply chain price volatility. This study seeks to explain unjustifiable price rises for vegetables, which are vital for nutritional balance and achieving daily dietary needs. To answer the research topic, the study uses qualitative and quantitative data. From January 2024 to May 2025, questionnaires, KIIs, and focus group talks were used to collect data in Bogura. Also studied were policy documents and market price notifications. According to the study, popular vegetables are more likely to fluctuate in wholesale and retail prices. In the actor and factor domains, wholesalers, retailers, and intermediaries caused the price increase. Due to policy gaps in market regulation frameworks, a lack of open monitoring, and inadequate institutional responsibility, these firms drive up prices to maximise profits. The study identified corruption by government officials and private market actors like wholesalers and merchants is essential to this issue. Ineffective traditional market management regulation led to the Directorate of National Consumer Rights Protection. A comprehensive policy framework that assures rigorous market regulation, transparency, and accountability to minimise unexpected and undesirable price rises while protecting consumer rights and happiness is proposed in this paper.